The Projection Targets of Medium Spiny Neurons Govern Cocaine-Evoked Synaptic Plasticity in the Nucleus Accumbens - Baimel, Corey (Cell Rep, 2019)
We examine synaptic connectivity and cocaine-evoked plasticity at specific networks within the nucleus accumbens (NAc). We identify distinct subpopulations of D1+ medium spiny neurons (MSNs) that project to either the ventral pallidum (D1+(VP)) or the ventral tegmental area (D1+(VTA)). We show that inputs from the ventral hippocampus (vHPC), but not the basolateral amygdala (BLA), are initially biased onto D1+(VTA) MSNs. However, repeated cocaine exposure eliminates the bias of vHPC inputs onto D1+(VTA) MSNs, while strengthening BLA inputs onto D1+(VP) MSNs. Our results reveal that connectivity and plasticity depend on the specific inputs and outputs of D1+ MSNs and highlight the complexity of cocaine-evoked circuit level adaptations in the NAc.